The cyborg utopia of the commons: Digital theatre as dissonance and collective resonance (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article presents a creative process, inspired by the text of Bertolt Brecht, The days of the Commune of Paris, held within the framework of the discipline of Staging, in the Degree in Theater of Universidades do Estado de Santa Catarina. Addressing the interruption of this creative path, determined by the COVID-19 pandemic, the article investigates the new strategies undertaken by the group, using videos and zoom's digital platform, to continue the creation, using, in this critical analysis, the concepts of utopia, from Thomas More, and from "cyborg", presented by Donna Haraway.
Keywords: Staging; Dramaturgy; Critical theory; Digital theatre; Epic theater